Rice (Oryza sativa L.) roots have iodate reduction activity in response to iodine - Kato, Shota; Wachi, Takanori; Yoshihira, Kei; Nakagawa, Takuya; Ishikawa, Akifumi; Takagi, Daichi; Tezuka, Aya; Yoshida, Hideharu; Yoshida, Satoshi; Sekimoto, Hitoshi; Takahashi, Michiko (Frontiers in Plant Science, 2013)
Although iodine is not an essential nutrient for higher plants, their roots take up and transport the element. However, the exact mechanisms involved in iodine uptake and metabolism in higher plants have yet to be elucidated. In this study, we compared two cultivars differing in iodine tolerance (“Nipponbare” and “Gohyakumangoku”) to increasing levels of I− and IO−3 in the root solutions of water-cultured rice (Oryza sativa L.). We found that IO−3 added to the root solutions was converted to I− in the presence of roots. Iodate reduction occurred over the course of several hours. Furthermore, the iodate reduction activity of “Nipponbare” (iodine-sensitive) and “Gohyakumangoku” (iodine-tolerant) roots increased after adding IO−3 or I−. The roots of barley and soybean also showed iodate reduction activity and the activity responded to iodine treatment either with IO−3 and I−. This study suggests that plant roots biologically reduce iodate to iodide and indicates that the iodate reduction activity of roots responds to external iodine conditions.